2015
DOI: 10.1021/acs.jpclett.5b00389
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity of CH3NH3PbI3 Perovskite

Abstract: Ferroelectricity has been believed to be an important but controversial origin of the excellent photovoltaic performance of organometal trihalide perovskites (OTPs). Here we investigate the ferroelectricity of a prototype OTP, CH3NH3PbI3 (MAPbI3), both theoretically and experimentally. Our first-principles calculations based on 3-D periodic boundary conditions reveal that a ferroelectric structure with polarization of ∼8 μC/cm(2) is the globally stable one among all possible tetragonal structures; however, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
222
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(235 citation statements)
references
References 38 publications
10
222
1
2
Order By: Relevance
“…[7][8][9] The organohalide lead perovskite materials currently yielding very promising photovoltaic device effi ciencies are also reported to be ferroelectric, although the importance of their ferroelectric properties in achieving such high effi ciencies is currently unclear. [10][11][12][13] In almost all cases where enhanced solar conversion performance has been attributed to ferroelectric materials properties, this enhancement has been assigned to reduced recombination losses. [ 11,14,15 ] However to date, to the best of our knowledge, there are no reports directly probing the extent to which spontaneous polarization can indeed increase charge carrier lifetimes.…”
Section: Doi: 101002/adma201601238mentioning
confidence: 99%
“…[7][8][9] The organohalide lead perovskite materials currently yielding very promising photovoltaic device effi ciencies are also reported to be ferroelectric, although the importance of their ferroelectric properties in achieving such high effi ciencies is currently unclear. [10][11][12][13] In almost all cases where enhanced solar conversion performance has been attributed to ferroelectric materials properties, this enhancement has been assigned to reduced recombination losses. [ 11,14,15 ] However to date, to the best of our knowledge, there are no reports directly probing the extent to which spontaneous polarization can indeed increase charge carrier lifetimes.…”
Section: Doi: 101002/adma201601238mentioning
confidence: 99%
“…They confirmed that ferroelectric properties exist in OTP materials. By performing firstprinciples calculations, combining the classic point charge model and the Berry phase method, Fan et al [85] obtained consistent polarization of~8 µC cm −2 . This result suggests that a ferroelectric structure of~8 µC cm −2 in the mate-rial is the most stable.…”
Section: The Ferroelectricity Of Otpmentioning
confidence: 99%
“…Fan et al [85] concluded that OTP does not exhibit ferroelectricity based on the EP loop and PFM measurements. Beilsten et al [93] studied the conductivity hysteresis of CH3NH3PbI3 films using the double-wave method and obtained results that excluded the impact of the leakage current.…”
Section: The Ferroelectricity Of Otpmentioning
confidence: 99%
“…19,27,28 Recently, there have been numerous conflicting reports regarding ferroelectricity in perovskites. [29][30][31][32] The controversy over the ferroelectricity of methylammonium lead iodide (CH3NH3PbI3) perovskite layer closely resembles the dispute over the ferroelectricity of bananas 33 and highlights the extra care that should be taken in the interpretation of electrical polarization loops and the claim of ferroelectricity. 34 The prerequisite of ferroelectricity of a compound is that the crystal structure must be non-centrosymmetric hence exhibiting a strong optical second harmonic generation (SHG).…”
mentioning
confidence: 94%